Lung abscess due to Streptococcus pneumoniae simulating pulmonary tuberculosis: presentation of two cases - Alessandro Perazzo; Piergiorgio Gatto; Gianluca Ferraioli; Renata Senarega; Cornelius Barlascini; Mario Santo; Silvia Reali; Antonello Nicolini (Italian Journal of Medicine, 2014)
In the past, anaerobes were the most common cause of community-acquired lung abscess; Streptococcus species were the second most common cause. In recent years, this has changed. Klebsiella pneumoniae is now most common cause of community- acquired lung abscess, although Streptococcus species remain pathogen of major importance. We present two cases of pulmonary cavitation due to Streptococcus pneumoniae which resembled pulmonary tuberculosis with regards to their history and radiological findings. These are examples of a common diagnosis presenting in an uncommon way. Our cases had some peculiarities: they had a clinical picture strongly suggestive of pulmonary tuberculosis or lung cancer rather than necrotizing infectious pneumonia in patients with no comorbidities or underlying diseases (including oral or dental pathologies). Radiological findings did not help the clinicians: pulmonary tuberculosis was the first diagnostic hypothesis in both cases. An underlying lung cancer was excluded in the first case only after invasive pulmonary procedures.